Antibacterial Activity of Kecombrang Rod Extract (Etlingera elatior (Jack) R.M.Sm.) on Dental Plaque Bacteria Streptococcus mutans - Nani Suryani; Devi Nurjanah; Dimas Danang Indriatmoko (Department of Chemistry, Faculty of Sciences and Informatics, Jenderal Achmad Yani University, 2019)
Dental plaques are formed by biofilms that cover the surface of the tooth. Biofilm is a mucous layer consisting of millions of bacterial cells, saliva and food scraps. When biofilm formation is out of control, it will easily thicken on the tooth surface called plaque. This biofilm is a good place for colonization and growth of various types of bacteria, one of which is the Sterpotococcus mutans bacteria. S. mutans bacteria can form colonies that are firmly attached to the tooth surface and are cariogenic bacteria that are able to ferment sucrose (carbohydrates) into acid, reduce the pH of the tooth surface and cause tooth mineralization. So for the control of these bacteria, preparations containing antibacterials are used, one of which is natural ingredients, namely Kecombrang. The aim of this study was to determine the antibacterial activity of the Etlingera elatior (Jack) R.M.Sm. stem extract extracted by solvent based on the level of polarity. Antibacterial activity testing of extracts was divided into 5 groups, namely for n-hexane, ethyl acetate, ethanol extract 20, 40, 60 and 80%, positive control of minosep and negative control (DMSO). The test results showed that E. elatior (Jack) RMSm.) contained secondary metabolites of flavonoids, tannins, saponins, triterpenoids and alkaloids, ethyl acetate extracts with concentrations of 20, 40, 60 and 80%, having strong antibacterial activity against S. mutans of 17.22; 17,55; 17.77 and 18.55 mm, higher than the positive control of Minosep which has antibacterial activity of 16.55 mm.